Cardiopulmonary resuscitation missed by bystanders: Collateral damage of coronavirus disease 2019. Issue 9 (5th August 2022) - Stirparo, Giuseppe; Fagoni, Nazzareno; Bellini, Lorenzo; Oradini‐Alacreu, Aurea; Migliari, Maurizio; Villa, Guido Francesco; Botteri, Marco; Signorelli, Carlo; Sechi, Giuseppe Maria; Zoli, Alberto
Abstract: Objective: The coronavirus disease 2019 (COVID‐19) pandemic changed the time‐dependent cardiac arrest network. This study aims to understand whether the rescue standards of cardiopulmonary resuscitation (CPR) and out‐of‐hospital cardiac arrest (OHCA) were handled differently during pandemic compared to the previous year. Methods: Data for the years 2019 and 2020 were provided by the records of the Lombardy office of the Regional Agency for Emergency and Urgency. We analysed where the cardiac arrest occurred, when CPR started and whether the bystanders used public access to defibrillation (PAD). Results: During 2020, there was a reduction in CPRs performed by bystanders (odds ratio [OR] = 0.936 [95% confidence interval (CI95% ) 0.882–0.993], p =  .029) and in the return of spontaneous circulation (ROSC) (OR = 0.621 [CI95% 0.563–0.685], p <  .0001), while there was no significant reduction in the use of PAD. Analysing only March, the period of the first wave in Lombardy, the comparison shows a reduction in bystanders CPRs (OR = 0.727 [CI95% 0.602–0.877], p =  .0008), use of PAD (OR = 0.441 [CI95% 0.272–0.716], p =  .0009) and in ROSC (OR = 0.179 [CI95% 0.124–0.257], p <  .0001). These phenomena could be influenced by the different settings in which the OHCAs occurred; in fact, those that occurred in public places with a mandatory PAD were strongly reduced (OR = 0.49 [CI95%, 0.44–0.55], p <  .0001). Conclusions: COVID‐19 had a profound impact on the time‐dependant OHCA network. During the first pandemic wave, CPR and PAD used by bystanders decreased. The different contexts in which OHCAs occurred may partially explain these differences.